The Transient Receptor Potential Channel Yvc1 Deletion Recovers the Growth Defect of Calcineurin Mutant Under Endoplasmic Reticulum Stress in Candida albicans - Peng, Liping; Du, Jiawen; Zhang, Runfan; Zhu, Nali; Zhao, He; Zhao, Qiang; Yu, Qilin; Li, Mingchun (Frontiers in microbiology, 2021)
Transient receptor potential (TRP) channel Yvc1 was related with hyphal growth, oxidative stress response, and pathogenicity. Calcineurin subunit Cnb1 was activated immediately in yeasts when exposed to severe stimulation. However, the relationship between Yvc1 and Cnb1-governed calcium ions and endoplasmic reticulum (ER) stress response remains unrevealed. In this study, we found that the mutant cnb1 Δ/Δ was sensitive to TN, which was related with the overexpression of membrane calcium ion channels that could increase the cytosol calcium concentration. However, the growth of the cnb1 Δ/Δ yvc1 Δ/Δ mutant was recovered and its cell vitality was better than the cnb1 Δ/Δ strain. Meanwhile, the cellular calcium concentration was decreased and its fluctuation was weakened under ER stress in the cnb1 Δ/Δ yvc1 Δ/Δ strain. To verify the regulation role of Yvc1 in the calcium concentration, we found that the addition of CaCl 2 led to the worse viability, while the growth state was relieved under the treatment of EGTA in the cnb1 Δ/Δ strain. In conclusion, the deletion of YVC1 could reduce the cellular calcium and relieve the ER stress sensitivity of the cnb1 Δ/Δ strain. Thereby, our findings shed a novel light on the relationship between the Yvc1-governed cellular calcium concentration and ER stress response in C. albicans .